1985
DOI: 10.1007/bf01309398
|View full text |Cite
|
Sign up to set email alerts
|

Gastric morphology in ulcer patients receiving misoprostol

Abstract: The effects of misoprostol on human gastric antral mucosa were investigated in patients with established diagnoses of either gastric or duodenal ulcer. All patients had pretreatment biopsy. After starting treatment with misoprostol, antral biopsies were taken at four and eight weeks and were fixed in formaldehyde. Following fixation and routine tissue processing, the slides were stained with hematoxylin and eosin. A pathologist from the laboratory preparing the slides reviewed the slides and prepared surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
0
2
Order By: Relevance
“…The hypersecretion of mucus caused by the hyperplasia of the goblet cells in the crypts of Lieberkühn could contribute to the obstruction of the duodenal glands and to the resulting dilatation. It has been reported that human patients with gastric or duodenal ulcers have mild goblet cell hyperplasia in the duodenum 8 . However, only 1 sheep out of 6 in the current study had abomasal ulcers.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…The hypersecretion of mucus caused by the hyperplasia of the goblet cells in the crypts of Lieberkühn could contribute to the obstruction of the duodenal glands and to the resulting dilatation. It has been reported that human patients with gastric or duodenal ulcers have mild goblet cell hyperplasia in the duodenum 8 . However, only 1 sheep out of 6 in the current study had abomasal ulcers.…”
contrasting
confidence: 64%
“…It has been reported that human patients with gastric or duodenal ulcers have mild goblet cell hyperplasia in the duodenum. 8 However, only 1 sheep out of 6 in the current study had abomasal ulcers. The observed inflammation in the lamina propria could be related to the accumulation of feed material in the diverticula 7 and could contribute to early obstruction.…”
contrasting
confidence: 52%